Предмет: Математика,
автор: lizagitkova1
решить пример.......................................
Приложения:
Ответы
Автор ответа:
0
1. [3*(√6+1)-√6*(1-√6)]/(1-√6)*(√6+1)=[3√6+3-√6+(√6)²]/(1-6)=(2√6+9)/(-5)
2. [(2√6+9)/(-5)]*(9-2√6)=[9²-(2√6)²]/(-5)=(81-24)/(-5)=-57/5=-11,4
2. [(2√6+9)/(-5)]*(9-2√6)=[9²-(2√6)²]/(-5)=(81-24)/(-5)=-57/5=-11,4
Похожие вопросы
Предмет: Математика,
автор: anonim829
Предмет: Қазақ тiлi,
автор: moldir240818
Предмет: Қазақ тiлi,
автор: goha290986
Предмет: Математика,
автор: gunkov
Предмет: Химия,
автор: saliv40